Effectiveness of Village Community Empowerment Program Reducing Poverty in Palakka District - Andi Muhammad Yunus; Andi Asdar; Andi Cahaya; Feby Triadi; M. Awaluddin A (Public Resource Innovation Management and Excellence, 2024)
Poverty is a complex social problem and is still a challenge in various regions, including in Palakka District, Bone Regency, South Sulawesi. One of the efforts made to overcome this problem is through a village community empowerment program. This study aims to evaluate the effectiveness of community empowerment programs in poverty alleviation and identify more optimal strategies to improve community welfare. The method used in this study is a qualitative descriptive approach with a case study in Palakka District. Data collection techniques include in-depth interviews, observations, and documentation analysis. The results of the study indicate that the village community empowerment program has a positive impact on improving community welfare, especially through increasing individual capacity, access to entrepreneurship training, and increasing community income through productive businesses. However, the effectiveness of the program still faces several challenges, such as limited supporting infrastructure, limited market access, and lack of sustainable funding. This study confirms that active community participation, government support, and synergy with the private sector and non-governmental organizations are key factors in the success of community empowerment programs. Improvements are needed in policies and program implementation to be more oriented to local needs and ensure the sustainability of the program in the long term. With a more integrated and strategic approach, it is hoped that the village community empowerment program can be an effective solution in eradicating poverty sustainably in Palakka District, Bone Regency.